Character in Young Adult fiction: The example of Lyra in Philip Pullman’s His Dark Materials (1995-2000) and The Book of Dust (2017- ) - Virginie DOUGLAS (E-REA)
Few studies have examined the question of characters and the specific ways in which they are treated in children's literature. Yet the construction of the character is all the more important in novels for children and teenagers as a large proportion of these books focus on Bildung and personal development through the exploration of the transition from childhood to maturity.I examine the treatment of character in these books through the case study of young Lyra, Philip Pullman’s new Eve in His Dark Materials fantasy trilogy (1995-2000). On the one hand, the treatment of the character of Lyra belongs to a rather conventional novelistic tradition in several respects. But on the other hand, it also benefits from more innovative elements related with the possibilities offered by fantasy, a genre which is still at the height of popularity with young adults. Daemons, for instance, are animal creatures in Lyra’s familiar yet different world who are closely connected to their human counterparts and disclose their owners’ innermost nature while playing the protective part of totemic animals. This metaphor is one of the devices in the trilogy, along with the alethiometer—a compass-like symbol-reader—, through which the character of Lyra is revealed to the reader.The fact that Pullman’s work belongs to the genre of young adult fiction is also essential. This literature targeting a liminal age group whose boundaries are increasingly blurred, fragments its young characters’ evolution ad infinitum by following them step by step towards adulthood as a way to better dissect the mutations and metamorphoses of adolescence. Even if His Dark Materials identified puberty as a turning-point in the young protagonists’ process of growing up and construction of identity, it is significant that Pullman, who had already added a small companion book—entitled Lyra’s Oxford—to the trilogy’s literary universe, is still trying to explore the multiple dimensions of Lyra’s constantly shifting character: while book 1 of The Book of Dust, Pullman’s new trilogy, La Belle Sauvage (2017), is a prequel to His Dark Materials, which focuses on Lyra as a baby—before the action in Northern Lights takes place—, book 2, The Secret Commonwealth (2019), takes a closer look at Lyra once she has become a young woman, after her meeting with Will in His Dark Materials.